Análisis económico productivo de los planes de desarrollo de las parroquias rurales del cantón Las Lajas, provincia de El Oro - Malla Cordova, Arleth Matilde (Machala : Universidad Técnica de Machala, 2019)
When speaking of the rural term, they are very often considered as something that is outside the concern of central governments, due to the size of the different territories, so it is important to carry out a respective analysis regarding the degree of development of the different programs and projects focused on the productive economic sector established in the development and territorial planning plans of the rural parishes of Las Lajas canton. It is known that planning in our country was not one of the priorities that is why resources were not distributed and there was no further development.Due to various factors, since the Constitution of 2008, economic measures were established, whose purpose is to decentralize and establish powers to the different levels of government, in order that the resources arrive in a more effective manner and so rural parishes can from their perspective, from their requirements and needs, apply the plans and tend to the rural development that is so necessary for our people. The Canton Las Lajas is a canton whose population is mainly engaged in agricultural activities to develop and even more rural parishes of the canton that in our case study are three: La Libertad, El Paraíso and San Isidro, which have conditions adequate for the development of said activities; It is important that the different levels of government focus on various programs and projects that promote the sector and that the economy of the parishes resurface. For the development of the subject research methods and techniques were used such as: the inductive and the deductive, the analytical and the synthetic, as well as the techniques of the interview and the collection of data from direct sources which help us to verify and establish indicators that measure the progress of development and territorial planning plans. In the Organic Code of Territorial Organization, Autonomy and Decentralization, the different competences for the different levels of government are established, this is one of the documents where the focus will be on the degree of development of the programs and projects in the rural parochial governments . Indicators will be implemented for the most accurate evaluation and to be able to carry out a more precise analysis. The limited monitoring and evaluation of development plans and territorial planning make this research topic favorable for the implementation of possible solutions and thus help the development not only of the parishes but also of the country since the rural sectors are the source of production from the country.The results of the programs and projects of the economic and productive sectors are not being fulfilled, because priority has been given to other sectors of the economy and society, such as the elderly, to the guidance of young people and to the rural and urban infrastructure. sports courts, for which it is recommended, the rural and cantonal authorities focus more on the productive economic sector of rural parishes.
Al hablar del término rural muy común mente se tienen a considerar como algo que está afuera de la preocupación de los gobiernos centrales, debido a la dimensión que ocupan los distintos territorios, por ello resulta importante realizar un análisis respectivo en cuanto al grado de desarrollo de los distintos programas y proyectos enfocados en el sector económico productivo establecidos en los planes de desarrollo y ordenamiento territorial de las parroquias rurales del cantón Las Lajas. Es de conocimiento que la planificación en nuestro país no era una de las prioridades es por ello que los recursos no se distribuían y no había un mayor desarrollo. Debido a diversos factores, desde la Constitución del 2008, se establecieron medidas económicas, cuyo propósito consiste en descentralizar y establecer competencias a los distintos niveles de gobierno, con el fin de que los recursos lleguen de una manera más eficaz y así las parroquias rurales puedan desde su perspectiva, desde sus requerimientos y necesidades, aplicar los planes y tender al desarrollo rural que tanta falta hace a nuestros pueblos. El cantón Las Lajas es un cantón que su población principalmente se dedica a actividades Agropecuarias para poder desarrollarse y más aún las parroquias rurales del cantón que en nuestro caso de estudio son tres: La Libertad, El Paraíso y San Isidro, las cuales cuentan con condiciones adecuadas para el desarrollo de dichas actividades; es importante que los distintos niveles de gobierno se enfoquen en diversos programas y proyectos que fomenten el sector y que la economía de las parroquias resurja. Para el desarrollo del tema se utilizaron métodos y técnicas de investigación como son: el inductivo y el deductivo, el analítico y el sintético, así como las técnicas de la entrevista y la recolección de datos de fuentes directas las que nos ayudan a verificar y establecer indicadores que midan el avance de los planes de desarrollo y ordenamiento territorial. En el Código Orgánico de Organización Territorial, Autonomía y Descentralización, se establecen las distintas competencias para los diferentes niveles de gobierno, este es uno de los documentos en donde se enfocará para saber el grado de desarrollo de los programas y proyectos en los gobiernos parroquiales rurales. Se implementarán indicadores para la evaluación más exacta y poder realizar un análisis más preciso. El escaso seguimiento y evaluación de los planes de desarrollo y ordenamiento territorial hacen de este tema de investigación favorable para la implementación de posibles soluciones y así ayudar al desarrollo no solo de las parroquias sino también del país ya que los sectores rurales son la fuente de producción del país. Los resultados de los programas y proyectos de los sectores económicos y productivos no se están cumpliendo, porque se ha dado prioridad a otros sectores de la economía y de la sociedad, como a los adultos mayores, a la orientación de jóvenes y a la infraestructura víal y canchas deportivas, por lo que se recomienda, a las autoridades rurales y cantonales se enfoquen más en el sector económico productivo de las parroquias rurales.
Keywords: DESARROLLO; RURAL; INDICADORES; PLANIFICACIÓN